2011
DOI: 10.3122/jabfm.2011.02.100155
|View full text |Cite
|
Sign up to set email alerts
|

Observational Study of Buprenorphine Treatment of Opioid-Dependent Pregnant Women in a Family Medicine Residency: Reports on Maternal and Infant Outcomes

Abstract: Purpose: Within a family medicine residency, an outpatient buprenorphine treatment program was provided for pregnant women who were dependent on opioids. The purpose of this study was to investigate the outcomes of infants who were exposed to a range of doses of buprenorphine in utero and to determine how closely observed maternal/fetal outcomes (eg, method of delivery and infants requiring treatment for neonatal abstinence syndrome [NAS]) match those previously reported in the literature.Methods: This study c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…Consistent with expectations (O’Connor et al, 2011), NAS symptoms peaked on day 3 of life. More than half of the infants (24, 58.5%) required pharmacotherapy for NAS; of these 3 (12.5%) required a second medication to control NAS symptoms.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with expectations (O’Connor et al, 2011), NAS symptoms peaked on day 3 of life. More than half of the infants (24, 58.5%) required pharmacotherapy for NAS; of these 3 (12.5%) required a second medication to control NAS symptoms.…”
Section: Resultssupporting
confidence: 88%
“…Cord blood concentrations of active metabolites norbuprenorphine and buprenorphine-glucuronide have been positively related with incidence of NAS requiring pharmacotherapy (Shah et al, 2016). However, most previous research has not found a relationship between maternal buprenorphine dose per se and NAS severity as defined by duration/incidence of NAS treatment, peak NAS score or duration of hospital stay (O’Connor et al, 2011; Jones et al, 2014; Bakstad et al, 2009; Metz et al, 2011), although one report suggested a relationship between dose and maximal NAS score that was not significant when the NAS score was above zero (Lejeune et al, 2006). Most of these studies did not consider other substance use (Jones et al, 2014; Lejeune et al, 2006) or considered only limited other substance use (Metz et al, 2011), were retrospective (O’Connor et al, 2011), used self-reported measures of other substance use as opposed to toxicology screens (Bakstad et al, 2009), or had small numbers of participants (O’Connor et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…Buprenorphine is gradually becoming a first‐line treatment over methadone as availability increases . However, a few small studies have found that women on methadone may be less likely to relapse than women using buprenorphine . The higher cost of buprenorphine is also a consideration, although recently, some third‐party payers have begun to cover buprenorphine treatment …”
Section: Pharmacologic Treatmentmentioning
confidence: 99%
“…If symptoms persist 2 hours after the initial dose, an additional dose of 2 to 4 mg, up to a maximum of 16 mg in 24 hours, may be given . Dosing increases during the course of pregnancy are approximately 3 mg daily, primarily in the third trimester . The dosage is adjusted as withdrawal symptoms occur, keeping in mind that dosing requirements change as metabolic demands evolve during the pregnancy…”
Section: Pharmacologic Treatmentmentioning
confidence: 99%
“…Research on the relationship between buprenorphine dose and severity of NAS has typically failed to find any such relationship (Bakstad et al, 2009; Fischer et al, 2006; Kacinko et al, 2008, Lejeune et al, 2006; O'Connor et al, 2011). Metz et al (2011) also reported a failure to find relationships between buprenorphine dose and need for and amount of NAS medication, peak NAS score, and duration of NAS treatment in a sample of 26 neonates prenatally exposed to buprenorphine as part of comprehensive treatment program for maternal opioid use disorder.…”
Section: Introductionmentioning
confidence: 99%